QUALITY ASSESSMENT OF CASTING PRODUCT USING VARIOUS SAND MOULDING PROCESSES - Arif Ali Rind; Qadir Bux Jamali; Sajjad Bhangwar; Muhammad Kashif Abbasi; Muhammad Ramzan Luhur; Saira Akram Arain; Saqib Ali Malik (Policy Research Journal, 2025)
Casting defects can have a negative impact on a foundry's bottom line. At the simple level, they appear as rework costs or casting scrap costs. In many cases, however, casting defects can be found at the machining level, during the assembly stage or during the part use. The resulting value added and maintenance costs may sometimes be passed on to the foundry by the customer. The most common foundry defects in three types of castings are discussed in this section. Number of defective castings and styles of defective castings was observed during the year Sand inclusions and variables that can affect the source of sand inclusions have been given attention. During the wet moulding process the mould was placed in the room temperature and melted aluminum was poured into cavity. The casted product was very rough and having lot of defects due to the gas bubbles caused the cavities in the product surface. That material cannot be analyzed for the surface roughness test due to high defects. Total three readings of both processes were carried out, therefore for specimen of wet moulding (W1) at 10/100 mm depth, have the maximum surface roughness value of 4.88 μm,.For specimen of wet moulding (W2) at 10/100 mm depth, have the maximum surface roughness value of 4.43 μm, It was found that the casting with dry sand moulding have good surface finishing value as compared to the wet sand moulding.